(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The present article examines the pedagogical and psychological issues of andragogical education, emphasizing the theoretical foundations, principles of adult learning, motivational factors, psychological characteristics of adult learners, and contemporary challenges associated with implementing effective adult education programs. Special attention is paid to learner-centered approaches, self-directed learning, intrinsic motivation, and the role of digital technologies in modern andragogical practices. The article also discusses the significance of psychological support, educational environments, and instructional methodologies that promote adults’ personal and professional development. The findings suggest that effective andragogical education requires the integration of pedagogical principles with psychological understanding in order to create flexible, inclusive, and motivating learning environments.